The Windermere children [videorecording (DVD)] - Kretschmann, Thomas, 1962-; Garai, Romola, 1982-; McInnerny, Tim; Glen, Iain, 1961- (PBS, 2020)
Based on an extraordinary, untold true story of hope, this moving and ultimately redemptive story follows child survivors of the Nazi Holocaust and the remarkable team who were responsible for helping these children rebuild their lives as they forge friendships that will become a lifeline to a better future.